Factors for burnout in high school coaches - Bradford, S. H.; Keshok, C. M. (Research Quarterly for Exercise and Sport, 2009)
Purpose: The purpose of this study was to identify the degree of burnout experienced by head varsity high school coaches based on sports classifications coached.